(* Title: Big Sum over Finite Sets in Abelian Semigroups Author: Walter Guttmann Maintainer: Walter Guttmann *) (* Title: HOL/Groups_Big.thy Author: Tobias Nipkow Author: Lawrence C Paulson Author: Markus Wenzel Author: Jeremy Avigad *) section \Big Sum over Finite Sets in Abelian Semigroups\ theory Semigroups_Big imports Main begin text \ This theory is based on Isabelle/HOL's \Groups_Big.thy\ written by T. Nipkow, L. C. Paulson, M. Wenzel and J. Avigad. We have generalised a selection of its results from Abelian monoids to Abelian semigroups with an element that is a unit on the image of the semigroup operation. \ subsection \Generic Abelian semigroup operation over a set\ locale abel_semigroup_set = abel_semigroup + fixes z :: 'a ("\<^bold>1") assumes z_neutral [simp]: "x \<^bold>* y \<^bold>* \<^bold>1 = x \<^bold>* y" assumes z_idem [simp]: "\<^bold>1 \<^bold>* \<^bold>1 = \<^bold>1" begin interpretation comp_fun_commute f by standard (simp add: fun_eq_iff left_commute) interpretation comp?: comp_fun_commute "f \ g" by (fact comp_comp_fun_commute) definition F :: "('b \ 'a) \ 'b set \ 'a" where eq_fold: "F g A = Finite_Set.fold (f \ g) \<^bold>1 A" lemma infinite [simp]: "\ finite A \ F g A = \<^bold>1" by (simp add: eq_fold) lemma empty [simp]: "F g {} = \<^bold>1" by (simp add: eq_fold) lemma insert [simp]: "finite A \ x \ A \ F g (insert x A) = g x \<^bold>* F g A" by (simp add: eq_fold) lemma remove: assumes "finite A" and "x \ A" shows "F g A = g x \<^bold>* F g (A - {x})" proof - from \x \ A\ obtain B where B: "A = insert x B" and "x \ B" by (auto dest: mk_disjoint_insert) moreover from \finite A\ B have "finite B" by simp ultimately show ?thesis by simp qed lemma insert_remove: "finite A \ F g (insert x A) = g x \<^bold>* F g (A - {x})" by (cases "x \ A") (simp_all add: remove insert_absorb) lemma insert_if: "finite A \ F g (insert x A) = (if x \ A then F g A else g x \<^bold>* F g A)" by (cases "x \ A") (simp_all add: insert_absorb) lemma neutral: "\x\A. g x = \<^bold>1 \ F g A = \<^bold>1" by (induct A rule: infinite_finite_induct) simp_all lemma neutral_const [simp]: "F (\_. \<^bold>1) A = \<^bold>1" by (simp add: neutral) lemma F_one [simp]: "F g A \<^bold>* \<^bold>1 = F g A" proof - have "\f b B. F f (insert (b::'b) B) \<^bold>* \<^bold>1 = F f (insert b B) \ infinite B" using insert_remove by fastforce then show ?thesis by (metis (no_types) all_not_in_conv empty z_idem infinite insert_if) qed lemma one_F [simp]: "\<^bold>1 \<^bold>* F g A = F g A" using F_one commute by auto lemma F_g_one [simp]: "F (\x . g x \<^bold>* \<^bold>1) A = F g A" apply (induct A rule: infinite_finite_induct) apply simp apply simp by (metis one_F assoc insert) lemma union_inter: assumes "finite A" and "finite B" shows "F g (A \ B) \<^bold>* F g (A \ B) = F g A \<^bold>* F g B" \ \The reversed orientation looks more natural, but LOOPS as a simprule!\ using assms proof (induct A) case empty then show ?case by simp next case (insert x A) then show ?case by (auto simp: insert_absorb Int_insert_left commute [of _ "g x"] assoc left_commute) qed corollary union_inter_neutral: assumes "finite A" and "finite B" and "\x \ A \ B. g x = \<^bold>1" shows "F g (A \ B) = F g A \<^bold>* F g B" using assms by (simp add: union_inter [symmetric] neutral) corollary union_disjoint: assumes "finite A" and "finite B" assumes "A \ B = {}" shows "F g (A \ B) = F g A \<^bold>* F g B" using assms by (simp add: union_inter_neutral) lemma union_diff2: assumes "finite A" and "finite B" shows "F g (A \ B) = F g (A - B) \<^bold>* F g (B - A) \<^bold>* F g (A \ B)" proof - have "A \ B = A - B \ (B - A) \ A \ B" by auto with assms show ?thesis by simp (subst union_disjoint, auto)+ qed lemma subset_diff: assumes "B \ A" and "finite A" shows "F g A = F g (A - B) \<^bold>* F g B" proof - from assms have "finite (A - B)" by auto moreover from assms have "finite B" by (rule finite_subset) moreover from assms have "(A - B) \ B = {}" by auto ultimately have "F g (A - B \ B) = F g (A - B) \<^bold>* F g B" by (rule union_disjoint) moreover from assms have "A \ B = A" by auto ultimately show ?thesis by simp qed lemma setdiff_irrelevant: assumes "finite A" shows "F g (A - {x. g x = z}) = F g A" using assms by (induct A) (simp_all add: insert_Diff_if) lemma not_neutral_contains_not_neutral: assumes "F g A \ \<^bold>1" obtains a where "a \ A" and "g a \ \<^bold>1" proof - from assms have "\a\A. g a \ \<^bold>1" proof (induct A rule: infinite_finite_induct) case infinite then show ?case by simp next case empty then show ?case by simp next case (insert a A) then show ?case by fastforce qed with that show thesis by blast qed lemma reindex: assumes "inj_on h A" shows "F g (h ` A) = F (g \ h) A" proof (cases "finite A") case True with assms show ?thesis by (simp add: eq_fold fold_image comp_assoc) next case False with assms have "\ finite (h ` A)" by (blast dest: finite_imageD) with False show ?thesis by simp qed lemma cong [fundef_cong]: assumes "A = B" assumes g_h: "\x. x \ B \ g x = h x" shows "F g A = F h B" using g_h unfolding \A = B\ by (induct B rule: infinite_finite_induct) auto lemma strong_cong [cong]: assumes "A = B" "\x. x \ B =simp=> g x = h x" shows "F (\x. g x) A = F (\x. h x) B" by (rule cong) (use assms in \simp_all add: simp_implies_def\) lemma reindex_cong: assumes "inj_on l B" assumes "A = l ` B" assumes "\x. x \ B \ g (l x) = h x" shows "F g A = F h B" using assms by (simp add: reindex) lemma UNION_disjoint: assumes "finite I" and "\i\I. finite (A i)" and "\i\I. \j\I. i \ j \ A i \ A j = {}" shows "F g (\(A ` I)) = F (\x. F g (A x)) I" apply (insert assms) apply (induct rule: finite_induct) apply simp apply atomize apply (subgoal_tac "\i\Fa. x \ i") prefer 2 apply blast apply (subgoal_tac "A x \ \(A ` Fa) = {}") prefer 2 apply blast apply (simp add: union_disjoint) done lemma Union_disjoint: assumes "\A\C. finite A" "\A\C. \B\C. A \ B \ A \ B = {}" shows "F g (\C) = (F \ F) g C" proof (cases "finite C") case True from UNION_disjoint [OF this assms] show ?thesis by simp next case False then show ?thesis by (auto dest: finite_UnionD intro: infinite) qed lemma distrib: "F (\x. g x \<^bold>* h x) A = F g A \<^bold>* F h A" by (induct A rule: infinite_finite_induct) (simp_all add: assoc commute left_commute) lemma Sigma: "finite A \ \x\A. finite (B x) \ F (\x. F (g x) (B x)) A = F (case_prod g) (SIGMA x:A. B x)" apply (subst Sigma_def) apply (subst UNION_disjoint) apply assumption apply simp apply blast apply (rule cong) apply rule apply (simp add: fun_eq_iff) apply (subst UNION_disjoint) apply simp apply simp apply blast apply (simp add: comp_def) done lemma related: assumes Re: "R \<^bold>1 \<^bold>1" and Rop: "\x1 y1 x2 y2. R x1 x2 \ R y1 y2 \ R (x1 \<^bold>* y1) (x2 \<^bold>* y2)" and fin: "finite S" and R_h_g: "\x\S. R (h x) (g x)" shows "R (F h S) (F g S)" using fin by (rule finite_subset_induct) (use assms in auto) lemma mono_neutral_cong_left: assumes "finite T" and "S \ T" and "\i \ T - S. h i = \<^bold>1" and "\x. x \ S \ g x = h x" shows "F g S = F h T" proof- have eq: "T = S \ (T - S)" using \S \ T\ by blast have d: "S \ (T - S) = {}" using \S \ T\ by blast from \finite T\ \S \ T\ have f: "finite S" "finite (T - S)" by (auto intro: finite_subset) show ?thesis using assms(4) by (simp add: union_disjoint [OF f d, unfolded eq [symmetric]] neutral [OF assms(3)]) qed lemma mono_neutral_cong_right: "finite T \ S \ T \ \i \ T - S. g i = \<^bold>1 \ (\x. x \ S \ g x = h x) \ F g T = F h S" by (auto intro!: mono_neutral_cong_left [symmetric]) lemma mono_neutral_left: "finite T \ S \ T \ \i \ T - S. g i = \<^bold>1 \ F g S = F g T" by (blast intro: mono_neutral_cong_left) lemma mono_neutral_right: "finite T \ S \ T \ \i \ T - S. g i = \<^bold>1 \ F g T = F g S" by (blast intro!: mono_neutral_left [symmetric]) lemma mono_neutral_cong: assumes [simp]: "finite T" "finite S" and *: "\i. i \ T - S \ h i = \<^bold>1" "\i. i \ S - T \ g i = \<^bold>1" and gh: "\x. x \ S \ T \ g x = h x" shows "F g S = F h T" proof- have "F g S = F g (S \ T)" by(rule mono_neutral_right)(auto intro: *) also have "\ = F h (S \ T)" using refl gh by(rule cong) also have "\ = F h T" by(rule mono_neutral_left)(auto intro: *) finally show ?thesis . qed lemma reindex_bij_betw: "bij_betw h S T \ F (\x. g (h x)) S = F g T" by (auto simp: bij_betw_def reindex) lemma reindex_bij_witness: assumes witness: "\a. a \ S \ i (j a) = a" "\a. a \ S \ j a \ T" "\b. b \ T \ j (i b) = b" "\b. b \ T \ i b \ S" assumes eq: "\a. a \ S \ h (j a) = g a" shows "F g S = F h T" proof - have "bij_betw j S T" using bij_betw_byWitness[where A=S and f=j and f'=i and A'=T] witness by auto moreover have "F g S = F (\x. h (j x)) S" by (intro cong) (auto simp: eq) ultimately show ?thesis by (simp add: reindex_bij_betw) qed lemma reindex_bij_betw_not_neutral: assumes fin: "finite S'" "finite T'" assumes bij: "bij_betw h (S - S') (T - T')" assumes nn: "\a. a \ S' \ g (h a) = z" "\b. b \ T' \ g b = z" shows "F (\x. g (h x)) S = F g T" proof - have [simp]: "finite S \ finite T" using bij_betw_finite[OF bij] fin by auto show ?thesis proof (cases "finite S") case True with nn have "F (\x. g (h x)) S = F (\x. g (h x)) (S - S')" by (intro mono_neutral_cong_right) auto also have "\ = F g (T - T')" using bij by (rule reindex_bij_betw) also have "\ = F g T" using nn \finite S\ by (intro mono_neutral_cong_left) auto finally show ?thesis . next case False then show ?thesis by simp qed qed lemma reindex_nontrivial: assumes "finite A" and nz: "\x y. x \ A \ y \ A \ x \ y \ h x = h y \ g (h x) = \<^bold>1" shows "F g (h ` A) = F (g \ h) A" proof (subst reindex_bij_betw_not_neutral [symmetric]) show "bij_betw h (A - {x \ A. (g \ h) x = \<^bold>1}) (h ` A - h ` {x \ A. (g \ h) x = \<^bold>1})" using nz by (auto intro!: inj_onI simp: bij_betw_def) qed (use \finite A\ in auto) lemma reindex_bij_witness_not_neutral: assumes fin: "finite S'" "finite T'" assumes witness: "\a. a \ S - S' \ i (j a) = a" "\a. a \ S - S' \ j a \ T - T'" "\b. b \ T - T' \ j (i b) = b" "\b. b \ T - T' \ i b \ S - S'" assumes nn: "\a. a \ S' \ g a = z" "\b. b \ T' \ h b = z" assumes eq: "\a. a \ S \ h (j a) = g a" shows "F g S = F h T" proof - have bij: "bij_betw j (S - (S' \ S)) (T - (T' \ T))" using witness by (intro bij_betw_byWitness[where f'=i]) auto have F_eq: "F g S = F (\x. h (j x)) S" by (intro cong) (auto simp: eq) show ?thesis unfolding F_eq using fin nn eq by (intro reindex_bij_betw_not_neutral[OF _ _ bij]) auto qed lemma delta_remove: assumes fS: "finite S" shows "F (\k. if k = a then b k else c k) S = (if a \ S then b a \<^bold>* F c (S-{a}) else F c (S-{a}))" proof - let ?f = "(\k. if k = a then b k else c k)" show ?thesis proof (cases "a \ S") case False then have "\k\S. ?f k = c k" by simp with False show ?thesis by simp next case True let ?A = "S - {a}" let ?B = "{a}" from True have eq: "S = ?A \ ?B" by blast have dj: "?A \ ?B = {}" by simp from fS have fAB: "finite ?A" "finite ?B" by auto have "F ?f S = F ?f ?A \<^bold>* F ?f ?B" using union_disjoint [OF fAB dj, of ?f, unfolded eq [symmetric]] by simp with True show ?thesis using abel_semigroup_set.remove abel_semigroup_set_axioms fS by fastforce qed qed lemma delta [simp]: assumes fS: "finite S" shows "F (\k. if k = a then b k else \<^bold>1) S = (if a \ S then b a \<^bold>* \<^bold>1 else \<^bold>1)" by (simp add: delta_remove [OF assms]) lemma delta' [simp]: assumes fin: "finite S" shows "F (\k. if a = k then b k else \<^bold>1) S = (if a \ S then b a \<^bold>* \<^bold>1 else \<^bold>1)" using delta [OF fin, of a b, symmetric] by (auto intro: cong) lemma If_cases: fixes P :: "'b \ bool" and g h :: "'b \ 'a" assumes fin: "finite A" shows "F (\x. if P x then h x else g x) A = F h (A \ {x. P x}) \<^bold>* F g (A \ - {x. P x})" proof - have a: "A = A \ {x. P x} \ A \ -{x. P x}" "(A \ {x. P x}) \ (A \ -{x. P x}) = {}" by blast+ from fin have f: "finite (A \ {x. P x})" "finite (A \ -{x. P x})" by auto let ?g = "\x. if P x then h x else g x" from union_disjoint [OF f a(2), of ?g] a(1) show ?thesis by (subst (1 2) cong) simp_all qed lemma cartesian_product: "F (\x. F (g x) B) A = F (case_prod g) (A \ B)" apply (rule sym) apply (cases "finite A") apply (cases "finite B") apply (simp add: Sigma) apply (cases "A = {}") apply simp apply simp apply (auto intro: infinite dest: finite_cartesian_productD2) apply (cases "B = {}") apply (auto intro: infinite dest: finite_cartesian_productD1) done lemma inter_restrict: assumes "finite A" shows "F g (A \ B) = F (\x. if x \ B then g x else \<^bold>1) A" proof - let ?g = "\x. if x \ A \ B then g x else \<^bold>1" have "\i\A - A \ B. (if i \ A \ B then g i else \<^bold>1) = \<^bold>1" by simp moreover have "A \ B \ A" by blast ultimately have "F ?g (A \ B) = F ?g A" using \finite A\ by (intro mono_neutral_left) auto then show ?thesis by simp qed lemma inter_filter: "finite A \ F g {x \ A. P x} = F (\x. if P x then g x else \<^bold>1) A" by (simp add: inter_restrict [symmetric, of A "{x. P x}" g, simplified mem_Collect_eq] Int_def) lemma Union_comp: assumes "\A \ B. finite A" and "\A1 A2 x. A1 \ B \ A2 \ B \ A1 \ A2 \ x \ A1 \ x \ A2 \ g x = \<^bold>1" shows "F g (\B) = (F \ F) g B" using assms proof (induct B rule: infinite_finite_induct) case (infinite A) then have "\ finite (\A)" by (blast dest: finite_UnionD) with infinite show ?case by simp next case empty then show ?case by simp next case (insert A B) then have "finite A" "finite B" "finite (\B)" "A \ B" and "\x\A \ \B. g x = \<^bold>1" and H: "F g (\B) = (F \ F) g B" by auto then have "F g (A \ \B) = F g A \<^bold>* F g (\B)" by (simp add: union_inter_neutral) with \finite B\ \A \ B\ show ?case by (simp add: H) qed lemma swap: "F (\i. F (g i) B) A = F (\j. F (\i. g i j) A) B" unfolding cartesian_product by (rule reindex_bij_witness [where i = "\(i, j). (j, i)" and j = "\(i, j). (j, i)"]) auto lemma swap_restrict: "finite A \ finite B \ F (\x. F (g x) {y. y \ B \ R x y}) A = F (\y. F (\x. g x y) {x. x \ A \ R x y}) B" by (simp add: inter_filter) (rule swap) lemma Plus: fixes A :: "'b set" and B :: "'c set" assumes fin: "finite A" "finite B" shows "F g (A <+> B) = F (g \ Inl) A \<^bold>* F (g \ Inr) B" proof - have "A <+> B = Inl ` A \ Inr ` B" by auto moreover from fin have "finite (Inl ` A)" "finite (Inr ` B)" by auto moreover have "Inl ` A \ Inr ` B = {}" by auto moreover have "inj_on Inl A" "inj_on Inr B" by (auto intro: inj_onI) ultimately show ?thesis using fin by (simp add: union_disjoint reindex) qed lemma same_carrier: assumes "finite C" assumes subset: "A \ C" "B \ C" assumes trivial: "\a. a \ C - A \ g a = \<^bold>1" "\b. b \ C - B \ h b = \<^bold>1" shows "F g A = F h B \ F g C = F h C" proof - have "finite A" and "finite B" and "finite (C - A)" and "finite (C - B)" using \finite C\ subset by (auto elim: finite_subset) from subset have [simp]: "A - (C - A) = A" by auto from subset have [simp]: "B - (C - B) = B" by auto from subset have "C = A \ (C - A)" by auto then have "F g C = F g (A \ (C - A))" by simp also have "\ = F g (A - (C - A)) \<^bold>* F g (C - A - A) \<^bold>* F g (A \ (C - A))" using \finite A\ \finite (C - A)\ by (simp only: union_diff2) finally have *: "F g C = F g A" using trivial by simp from subset have "C = B \ (C - B)" by auto then have "F h C = F h (B \ (C - B))" by simp also have "\ = F h (B - (C - B)) \<^bold>* F h (C - B - B) \<^bold>* F h (B \ (C - B))" using \finite B\ \finite (C - B)\ by (simp only: union_diff2) finally have "F h C = F h B" using trivial by simp with * show ?thesis by simp qed lemma same_carrierI: assumes "finite C" assumes subset: "A \ C" "B \ C" assumes trivial: "\a. a \ C - A \ g a = \<^bold>1" "\b. b \ C - B \ h b = \<^bold>1" assumes "F g C = F h C" shows "F g A = F h B" using assms same_carrier [of C A B] by simp end subsection \Generalized summation over a set\ no_notation Sum ("\") class ab_semigroup_add_0 = zero + ab_semigroup_add + assumes zero_neutral [simp]: "x + y + 0 = x + y" assumes zero_idem [simp]: "0 + 0 = 0" begin sublocale sum_0: abel_semigroup_set plus 0 defines sum_0 = sum_0.F by unfold_locales simp_all abbreviation Sum_0 ("\") where "\ \ sum_0 (\x. x)" end context comm_monoid_add begin subclass ab_semigroup_add_0 by unfold_locales simp_all end text \Now: lots of fancy syntax. First, @{term "sum_0 (\x. e) A"} is written \\x\A. e\.\ syntax (ASCII) "_sum" :: "pttrn \ 'a set \ 'b \ 'b::comm_monoid_add" ("(3SUM (_/:_)./ _)" [0, 51, 10] 10) syntax "_sum" :: "pttrn \ 'a set \ 'b \ 'b::comm_monoid_add" ("(2\(_/\_)./ _)" [0, 51, 10] 10) translations \ \Beware of argument permutation!\ "\i\A. b" \ "CONST sum_0 (\i. b) A" text \Instead of @{term"\x\{x. P}. e"} we introduce the shorter \\x|P. e\.\ syntax (ASCII) "_qsum" :: "pttrn \ bool \ 'a \ 'a" ("(3SUM _ |/ _./ _)" [0, 0, 10] 10) syntax "_qsum" :: "pttrn \ bool \ 'a \ 'a" ("(2\_ | (_)./ _)" [0, 0, 10] 10) translations "\x|P. t" => "CONST sum_0 (\x. t) {x. P}" print_translation \ let fun sum_tr' [Abs (x, Tx, t), Const (@{const_syntax Collect}, _) $ Abs (y, Ty, P)] = if x <> y then raise Match else let val x' = Syntax_Trans.mark_bound_body (x, Tx); val t' = subst_bound (x', t); val P' = subst_bound (x', P); in Syntax.const @{syntax_const "_qsum"} $ Syntax_Trans.mark_bound_abs (x, Tx) $ P' $ t' end | sum_tr' _ = raise Match; in [(@{const_syntax sum_0}, K sum_tr')] end \ lemma (in ab_semigroup_add_0) sum_image_gen_0: assumes fin: "finite S" shows "sum_0 g S = sum_0 (\y. sum_0 g {x. x \ S \ f x = y}) (f ` S)" proof - have "{y. y\ f`S \ f x = y} = {f x}" if "x \ S" for x using that by auto then have "sum_0 g S = sum_0 (\x. sum_0 (\y. g x) {y. y\ f`S \ f x = y}) S" by simp also have "\ = sum_0 (\y. sum_0 g {x. x \ S \ f x = y}) (f ` S)" by (rule sum_0.swap_restrict [OF fin finite_imageI [OF fin]]) finally show ?thesis . qed subsubsection \Properties in more restricted classes of structures\ lemma sum_Un2: assumes "finite (A \ B)" shows "sum_0 f (A \ B) = sum_0 f (A - B) + sum_0 f (B - A) + sum_0 f (A \ B)" proof - have "A \ B = A - B \ (B - A) \ A \ B" by auto with assms show ?thesis by simp (subst sum_0.union_disjoint, auto)+ qed class ordered_ab_semigroup_add_0 = ab_semigroup_add_0 + ordered_ab_semigroup_add begin lemma add_nonneg_nonneg [simp]: "0 \ a \ 0 \ b \ 0 \ a + b" using add_mono[of 0 a 0 b] by simp lemma add_nonpos_nonpos: "a \ 0 \ b \ 0 \ a + b \ 0" using add_mono[of a 0 b 0] by simp end lemma (in ordered_ab_semigroup_add_0) sum_mono: "(\i. i\K \ f i \ g i) \ (\i\K. f i) \ (\i\K. g i)" by (induct K rule: infinite_finite_induct) (use add_mono in auto) lemma (in ordered_ab_semigroup_add_0) sum_mono_00: "(\i. i\K \ f i + 0 \ g i + 0) \ (\i\K. f i) \ (\i\K. g i)" proof (induct K rule: infinite_finite_induct) case (infinite A) then show ?case by simp next case empty then show ?case by simp next case (insert x F) then show ?case proof - fix x :: 'b and F :: "'b set" assume a1: "finite F" assume a2: "x \ F" assume a3: "(\i. i \ F \ f i + 0 \ g i + 0) \ sum_0 f F \ sum_0 g F" assume a4: "\i. i \ insert x F \ f i + 0 \ g i + 0" obtain bb :: 'b where f5: "bb \ F \ \ f bb + 0 \ g bb + 0 \ sum_0 f F \ sum_0 g F" using a3 by blast have "\b. x \ b \ f b + 0 \ g b + 0" using a4 by simp then have "\a aa. f x + 0 + a \ g x + 0 + aa \ \ a \ aa" using add_mono by blast then show "sum_0 f (insert x F) \ sum_0 g (insert x F)" using f5 a4 a2 a1 by (metis (no_types) add_assoc insert_iff sum_0.insert sum_0.one_F) qed qed lemma (in ordered_ab_semigroup_add_0) sum_mono_0: "(\i. i\K \ f i + 0 \ g i) \ (\i\K. f i) \ (\i\K. g i)" apply (rule sum_mono_00) by (metis add_right_mono zero_neutral) context ordered_ab_semigroup_add_0 begin lemma sum_nonneg: "(\x. x \ A \ 0 \ f x) \ 0 \ sum_0 f A" proof (induct A rule: infinite_finite_induct) case infinite then show ?case by simp next case empty then show ?case by simp next case (insert x F) then have "0 + 0 \ f x + sum_0 f F" by (blast intro: add_mono) with insert show ?case by simp qed lemma sum_nonpos: "(\x. x \ A \ f x \ 0) \ sum_0 f A \ 0" proof (induct A rule: infinite_finite_induct) case infinite then show ?case by simp next case empty then show ?case by simp next case (insert x F) then have "f x + sum_0 f F \ 0 + 0" by (blast intro: add_mono) with insert show ?case by simp qed lemma sum_mono2: assumes fin: "finite B" and sub: "A \ B" and nn: "\b. b \ B-A \ 0 \ f b" shows "sum_0 f A \ sum_0 f B" proof - have "sum_0 f A \ sum_0 f A + sum_0 f (B-A)" by (metis add_left_mono sum_0.F_one nn sum_nonneg) also from fin finite_subset[OF sub fin] have "\ = sum_0 f (A \ (B-A))" by (simp add: sum_0.union_disjoint del: Un_Diff_cancel) also from sub have "A \ (B-A) = B" by blast finally show ?thesis . qed lemma sum_le_included: assumes "finite s" "finite t" and "\y\t. 0 \ g y" "(\x\s. \y\t. i y = x \ f x \ g y)" shows "sum_0 f s \ sum_0 g t" proof - have "sum_0 f s \ sum_0 (\y. sum_0 g {x. x\t \ i x = y}) s" proof (rule sum_mono_0) fix y assume "y \ s" with assms obtain z where z: "z \ t" "y = i z" "f y \ g z" by auto hence "f y + 0 \ sum_0 g {z}" by (metis Diff_eq_empty_iff add_commute finite.simps add_left_mono sum_0.empty sum_0.insert_remove subset_insertI) also have "... \ sum_0 g {x \ t. i x = y}" apply (rule sum_mono2) using assms z by simp_all finally show "f y + 0 \ sum_0 g {x \ t. i x = y}" . qed also have "\ \ sum_0 (\y. sum_0 g {x. x\t \ i x = y}) (i ` t)" using assms(2-4) by (auto intro!: sum_mono2 sum_nonneg) also have "\ \ sum_0 g t" using assms by (auto simp: sum_image_gen_0[symmetric]) finally show ?thesis . qed end lemma sum_comp_morphism: "h 0 = 0 \ (\x y. h (x + y) = h x + h y) \ sum_0 (h \ g) A = h (sum_0 g A)" by (induct A rule: infinite_finite_induct) simp_all lemma sum_cong_Suc: assumes "0 \ A" "\x. Suc x \ A \ f (Suc x) = g (Suc x)" shows "sum_0 f A = sum_0 g A" proof (rule sum_0.cong) fix x assume "x \ A" with assms(1) show "f x = g x" by (cases x) (auto intro!: assms(2)) qed simp_all end